The “Neuro-Glial-Vascular” Unit: The Role of Glia in Neurovascular Unit Formation and Dysfunction - Kugler, Elisabeth C.; Greenwood, John; MacDonald, Ryan B. (Frontiers in Cell and Developmental Biology, 2021)
The neurovascular unit (NVU) is a complex multi-cellular structure consisting of endothelial cells, neurons, glia, smooth muscle cells, and pericytes. Each component is closely linked to each other, establishing a structural and functional unit, regulating central nervous system blood flow and energy metabolism as well as forming the blood-brain barrier and blood-retina barrier. As the name suggests, the “neuro” and “vascular” components of the NVU are well recognized. However, the role of glial cells in the formation and function of the NVU is not well understood. In the brain, astrocytes are the principal glia type, while in the retina, these are Müller glia (MG), both of which contact neurons and the vasculature, linking them spatio-functionally. Glial disruption, including those observed in gliosis, can precede overt neuronal and vascular pathologies suggesting glial disruption may underlie the pathogenesis of disease. In this review, we take a “glio-centric” view on the formation and function of the NVU in the retina and brain, how this changes in disease, and how advancing experimental techniques will help us address unanswered questions.